Extremely Rare Pulmonary Metastases of Skin Basal Cell Carcinoma: Report of Two Cases with Clinicopathological Features - Małgorzata Edyta Wojtyś; Kajetan Kiełbowski; Michał Kunc; Seweryn Adam Skrzyniarz; Piotr Lisowski; Rafał Becht; Paulina Żukowska; Konrad Ptaszyński; Janusz Wójcik (Biomedicines, 2023)
Basal cell carcinoma (BCC) is the most frequent human skin cancer, but metastasizing BCC (MBCC) is extremely rare, developing in approximately 0.0028% to 0.55% of BCC patients. Herein, we report two cases of pulmonary MBCC. The first one developed in a 72-year-old male who underwent surgical resection due to multiple recurrences and adjuvant radiotherapy. Immunohistochemistry showed that neoplastic cells expressed Ber-EP4, CK5/6, p63, EMA (focally), BCL-2, and CD10, but were negative for CK7, CK20, S100, estrogen and progesterone receptors, and TTF-1. The second case is a 64-year-old female treated with vismodegib. Clinicopathological features and differential diagnoses are described.